Managing Ebola and covid-19 crises for aviation industry: did industry learn how to learn? (Revista de Investigaciones Universidad del Quindío, 2022)
Learning is necessary for an organization to evolve, improve and innovate. We are all conditioned to benefit from the evident effects of our behaviors. After the first try, we do not touch the hot stove again. We are also conditioned to recognize complex scenarios and apply fast solutions. Companies are like humans and they also learn as people do. From this point of view, the aviation industry is discussed in this study beyond the learning loops approach of Agrysis which is an effective tool that encourages the kind of thought and action that is needed to transform an organization into a learning one. Turkish Airlines, EasyJet, Delta Airlines, Air China, United Airlines, China Eastern Airlines, China Southern Airlines, American Airlines, Southwest Airlines and Ryanair had chosen as the sample of this study and data collected from the annual reports of these companies was analyzed with document analysis methodology. By comparing the crisis management styles of the industry during Ebola and Covid-19 Diseases the question “did the industry learn how to learn?” tried to be answered and as a result, the study found that the way the industry responded to both crises had not gone too far from single loop learning, or in other words, the industry had only given a reaction to the actions on time and forgot every experience till the next crisis. In the end, the study discussed that single loop learning style of airline companies may be the reason for the rapid spread of those kinds of diseases all over the world.
Keywords: Learning Loops; Ebola Epidemic; Covid-19 Pandemic; Learning Organization; Aviation Industry